PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI PEMBELAJARAN STEM PADA MATA PELAJARAN MATEMATIKA MENGGUNAKAN RANCANGAN UNDERSTANDING BY DESIGN (UbD) DI KELAS V SEKOLAH DASAR - Annisa Dwi Yuniar; Yunita Sari; Nuhyal Ulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to increase students' learning motivation in Mathematics subjects with STEM learning using Understanding by Design (UbD) design. This research is a collaborative classroom action research with a qualitative descriptive approach consisting of 2 cycles, namely cycle 1 and cycle 2. The data source in this study is fifth grade students of SD Negeri Lamper Lor Semarang City, totaling 25 students in the 2024/2025 school year. Data collection techniques using observation. The results of this class action research showed that there was an increase from cycle 1 to cycle 2. Cycle 1 obtained a result of 85% in the good category, while cycle 2 obtained a result of 98% in the very good category. Thus, STEM learning can increase the learning motivation of students in the fifth grade of SD Negeri Lamper Lor Semarang City.